Biodiversity of Cyanophyceae from Amaravati Dam of Dhule district (Maharashtra) - S.N. Nandan, V.P. Patil* and (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> In aquatic ecosystems the flora and fauna interact with the biotic and abiotic factors in their habitat. Therefore flora and fauna are called biological indicators. Man made reservoirs like Dam reflect both terrestrial and aquatic environment as their construction involves superimposition of lentic water body on flowing water mass on the terrain. Algae constitute the main autotrophic component of the aquatic ecosystems. Change in algal community severely affect the species diversity. Biodiversity is greater in fresh water than in the most affected terrestrial ecosystem. So the present study shows biodiversity of Cyanophyceae from Amaravati Dam. Total 35 taxa belonging to 15 genera are discussed in present paper. The genera viz. Microcystis, Chroococcus, Gloeocapsa, Aphanocapsa, Synechococcus, Merismopedia, spirulina, Oscillatoria, Phormidium, Lyngbya, Nostoc, Anabaena, Plectonema, Homoethrix and calothrix. Ã‚Â 